Ludwik Tuberon de Crieva (Crijević) the Benedictine from Dubrovnik and his outline of the history of Turkey in the political memoir "Commentarii de temporibus suis" - Wróbel, Piotr (Balcanica Posnaniensia. Acta et studia, 2014)
One of the first writers from Dubrovnik who has attempted to write a comprehensive history of Turkey was Benedictine Louis de Crieva called Tuberon (1458-1527). In the sixth book of his political memoir <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Commentarii de temporibus suis, he provided a description of the origin, customs and outline of the history of the Turks. The analysis of his work leads to conclusion, that it was a response to a great interest in this topic in the 16th Europe. Moreover, the author attempted to give a full lecture of the history of Turks, although he knew very little about the history of sultans in the 14th and the first half of the 15th century.